Normalization Techniques For Translating Cultural - Specific Expressions (LSP International Journal, 2020)
For readability of audience in target culture (TC), cultural-specific expressions (CSEs) which have been embedded with specific characteristics, need specific techniques to transfer them into target language (TL). This study aims to identify normalization techniques (NTs) from domestication strategies to show that they are particularly necessary for CSE translation. Based on the previous studies of different scholars, the overlap between domestication and normalization is clarified, following by the clarification of the relation between normalization and the use of translator’s subjectivity, as well as the distinction between CSEs and universals for simple explanation on what normalization and CSE are. Last but not least, the overlapping NTs, classified from domestication strategies will be unified. Finally, illustration of normalization of CSEs, selected from Thai target text (TT) and its English source text (ST), The Da Vinci Code (DVC), a novel by Dan Brown, will give an overt explanation of how each NT is used to deal with CSEs in order to show relation between characteristics of CSEs and each NT. This will answer why NTs are necessary.